Aromatic polyimides from m-phenylene diamines containing pendant groups: synthesis and characterization - Pal, R. R.; Patil, P. S.; Dere, R. T.; Salunkhe, M. M.; Maldar, Noormahamad N.; Wadgaonkar, P. P. (Journal Applied Polymer Science, 2005)
Two diamine monomers, 4-[4-(1-methyl-1-phenyl)phenoxy]-1,3-(diamino benzene and 4-{-[(4-methylphenyl)sulfonyl]phenoxy}-1,3-diamino benzene, were synthesized, and both diamines were polycondensed with three commercial dianhydrides to obtain aromatic polyimides containing pendant groups. The polyimides were characterized by solubility tests, viscosity measurements, IR, H-1-NMR, and C-13- NMR spectroscopy, x-ray diffraction studies, and thermogravimetric analysis. The polymides had inherent viscosities of 0.33-0.58 dL/g in m-cresol at 30 +/- 0.1 degrees C. All the polyimides were amorphous and were soluble in solvents such as NNdimethylacetamide, N-methyl-2-pyrrolidone, N,N-dimethylformamide, and in-cresol. Thermogravimetric analysis of the polymides indicated no weight loss below 410 degrees C under a nitrogen atmosphere. (c) 2005 Wiley Periodicals, Inc.
Keywords: heteroatom-containing polymers; High performance polymers; polyimides

Anhydrous magnesium sulfate mediated solvent-free synthesis of dihydropyrimidin-2(1H)-ones at ambient temperature - Pore, D. M.; Desai, Uday V.; Thopate, T. S.; Wadgaonkar, P. P. (Australian Journal of Chemistry, 2007)
An anhydrous magnesium sulfate mediated solvent-free protocol is described for the synthesis of dihydropyrimidinones (Biginelli compounds) at ambient temperature.